2009
DOI: 10.4161/auto.5.8.10274
|View full text |Cite
|
Sign up to set email alerts
|

3D tomography reveals connections between the phagophore and endoplasmic reticulum

Abstract: Autophagosomes have been reported to form in the vicinity of the endoplasmic reticulum (ER). In many cases, the phagophore membrane is observed between two cisternae of rough ER, but it is not known whether these two membranes are directly connected. To investigate the relationship of the phagophore membrane and the ER, we used electron microscopic tomography of serum and amino acid starved normal rat kidney cells. The cells were fixed in glutaraldehyde and reduced osmium tetroxide and embedded in Epon. Dual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
453
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(482 citation statements)
references
References 20 publications
20
453
0
1
Order By: Relevance
“…These were named omegasomes, as DFCP1-positive rings often looked like Ω-shaped structures on the ER. The connection between isolation membranes and the ER was further confirmed by two independent studies using 3D tomographic imaging of isolation membranes [64,65]. These studies have shown that the cupshaped isolation membrane was tightly sandwiched by two sheets of ER.…”
Section: Autophagosome Formation On the Ersupporting
confidence: 49%
“…These were named omegasomes, as DFCP1-positive rings often looked like Ω-shaped structures on the ER. The connection between isolation membranes and the ER was further confirmed by two independent studies using 3D tomographic imaging of isolation membranes [64,65]. These studies have shown that the cupshaped isolation membrane was tightly sandwiched by two sheets of ER.…”
Section: Autophagosome Formation On the Ersupporting
confidence: 49%
“…Membranes derived from the Golgi, endoplasmic reticulum, mitochondria, and plasma membrane have been implicated as the source membranes. [20][21][22][23][24][25] It is possible that vesicles from multiple membrane sources may fuse heterotypically to generate APs. This early fusion steps may involve lipidhydrolyzing enzymes, possibly PLD.…”
Section: Discussionmentioning
confidence: 99%
“…Both rough ER and the outer nuclear leaflet have been identified as autophagosome formation sites [13][14][15] , but these vesicles might also be generated at other places. Two ubiquitin-like systems are involved in autophagosome formation at these sites with Atg8 and Atg12 as the ubiquitin-like molecules at their center 16 .…”
Section: T Cells Detect Infected or Transformed Cells Via Antigen Prementioning
confidence: 99%